2017
DOI: 10.3892/etm.2017.4658
|View full text |Cite
|
Sign up to set email alerts
|

Limb graft occlusion following endovascular aortic repair: Incidence, causes, treatment and prevention in a study cohort

Abstract: Abstract. The present study investigated the incidence, causes, treatment and prevention of limb graft occlusion following endovascular aortic repair (EVAR). A total of 66 cases of abdominal aortic aneurysm receiving EVAR at our department from January 2005 to December 2013 were enrolled. After EVAR, patients received routine antiplatelet therapy of 75 mg PLAVIX for 6 months and then 100 mg Aspirin for another 6 months by oral administration. According to previous clinical experiences, antiplatelet therapy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Limb thrombosis is a relatively common complication with a reported incidence of up to 10.6%. 6 Results of percutaneous treatment have been reported to be comparable with surgery in the treatment of limb thrombosis. [7][8][9] Spiliopoulos et al reported a technical success of 90.9% in 11 graft limb occlusions with no major complications.…”
Section: Discussionmentioning
confidence: 96%
“…Limb thrombosis is a relatively common complication with a reported incidence of up to 10.6%. 6 Results of percutaneous treatment have been reported to be comparable with surgery in the treatment of limb thrombosis. [7][8][9] Spiliopoulos et al reported a technical success of 90.9% in 11 graft limb occlusions with no major complications.…”
Section: Discussionmentioning
confidence: 96%
“…It represents a major cause of secondary intervention and the third most common cause for readmission. 1 Its incidence rates range from 0% to 7%. 2,3 Compared with unilateral limb occlusion, bilateral limb occlusion is relatively uncommon, with a reported incidence ranging from 0% to .6%.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The incidence of limb occlusion has been 2.3% after EVAR and has been linked to patient compliance and anatomic or device factors. 2 , 3 Treatment of this condition will often require open surgery. 2 …”
mentioning
confidence: 99%